Enhancing Cardiac Anomaly Detection through Deep Learning Autoencoder: An In-Depth Analysis Using the PTB Diagnostic ECG Database - Gregorius Airlangga (Universitas Islam Raden Rahmat, Malang, 2024)
Cardiovascular diseases are the leading cause of mortality worldwide, necessitating advancements in early anomaly detection from electrocardiogram (ECG) signals. This study introduces a novel convolutional neural network (CNN)-based autoencoder architecture that significantly outperforms traditional Multi-Layer Perceptron (MLP) models in detecting ECG anomalies. Our method capitalizes on unsupervised learning to discern between normal and pathological heartbeats with an accuracy of 71.16% and an F1 score of 73%. We address the challenge of imbalanced datasets by implementing a refined thresholding strategy for anomaly classification. Comparative analysis reveals that our model achieves superior precision, particularly in delineating true anomalies within ECG data. The proposed autoencoder architecture holds promise for clinical applications, offering a robust tool for enhancing diagnostic accuracy in cardiac care. Our research contributes to the growing body of knowledge in medical diagnostics, paving the way for improved patient outcomes through advanced deep learning techniques.